The Influence of Transaction Speed and Top-Up Facilities on the Decision to Use Fintech OVO with Partner Quantity as the Moderating Variable - Kamaruddin, Muhammad Junaid; Fauzi, Yoga; Elliyana, Ela (Journal of Business and Behavioural Entrepreneurship, 2023)
This study aims to analyze whether there is a significant influence between Transaction Speed and the Decision to Use and Partner Quantity on the Top Up Facility. The population in this study are all people who use fintech ovo in the Jakarta area. The sample of this research is 175 people. The type of data created is primary data using a questionnaire which is filled in directly by the respondents and then processing the data using Partial Least Square (PLS). Statistical results from research data processing show that transaction speed has a positive and significant effect, top up facilities can have a positive and significant effect, partner quantity is not yet significant, transaction speed has a positive and significant effect on usage decisions, top up facility has a positive and significant effect on usage decisions.